International outsourcing and the supply side productivity determinants - Arti Grover (Center for Economic Studies and ifo Institute (CESifo), 2007)
A service provider firm in an outsourcing relationship is distinct from a typical firm because it is not a stand alone organization and fits somewhere in between the value chain of its client's business. Thus, conventional factors like wages, capital, rent, energy consumption cannot appropriately determine a Business Process Outsourcing (BPO) firm's productivity. Academic research is silent on the factors that influence the performance of a BPO firm even though the issue is pertinent from the perspective of the host country, the sourcing firm, the global outsourcing industry and of course the service provider firm. In this paper, we embark on to explore these factors.
Keywords: L22; L23; L60; 330; Unternehmensdienstleistung; Service Provider; Outsourcing; Offshoring; Produktivität; Messung; Theorie; Indien